Trend and Spatial Distribution of Air Particulate Matter Pollution in Dhaka City (Journal of Bangladesh Academy of Sciences, 2010)
From the air particle (PM) collected from different locations of Dhaka city it has been foundthat about 30 - 50% of the PM10 mass (depending on location) is fine particles with aerodynamicdiameter less than 2.2 μm, which are mainly of anthropogenic origin and predominately fromtransport related sources. On the other hand, due to the meteorological reason and long-rangetransport during the wintertime, the PM concentrations remain much higher than the BangladeshNational Ambient Air Quality Standard (NAAQS).Key words: Spatial distribution; Air particulate matter; PollutionDOI: 10.3329/jbas.v34i1.5490Journal of Bangladesh Academy of Sciences, Vol.34, No.1, 33-48, 2010